2010
DOI: 10.1002/anie.201000843
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free, Aerobic Dioxygenation of Alkenes Using Hydroxamic Acids

Abstract: One dioxygenation please, hold the metal: In the presence of either oxygen or air as the sole oxidant and external oxygen atom source, a variety of unsaturated hydroxamic acids afford cyclic hydroxamates that are readily converted into 1,2‐diols, with the potential for high levels of reaction stereocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(22 citation statements)
references
References 36 publications
0
20
0
2
Order By: Relevance
“…In accordance with this free-radical mechanism, Schmidt and Alexanian more recently reported the aerobic dioxygenation of alkenyl N -aryl hydroxamic acids (Scheme 6) [21]. In this case dioxygenation proceeded under 1 atmosphere of O 2 alone, without any additional initiator being required.…”
Section: Reviewmentioning
confidence: 77%
“…In accordance with this free-radical mechanism, Schmidt and Alexanian more recently reported the aerobic dioxygenation of alkenyl N -aryl hydroxamic acids (Scheme 6) [21]. In this case dioxygenation proceeded under 1 atmosphere of O 2 alone, without any additional initiator being required.…”
Section: Reviewmentioning
confidence: 77%
“…18,19 A radical mechanism is consistent with the formation of 47 by a process involving combination of a C-5 radical with oxygen that would give hydroperoxide A (Scheme 2). Precedent for peroxide formation and reductive cleavage in/by 20,21 Unique to B, however, is the potential for ring-opening to the R-ketoamide C, which can reclose in a complementary fashion to form the 2-thiohydantoin 47, with experimental support for this sequence of events obtained as follows. Snider has reported that radicals generated in the presence of Mn(OAc) 3 /Cu(OAc) 2 can undergo further oxidation in which the resulting cation is trapped by acetic acid.…”
Section: 15mentioning
confidence: 98%
“…This appealing metal-free protocol evolved into enantioselective iodolactonization by using chiral amides or esters. The catalytic asymmetric halogen lactonization, as an emerging area, also attracted a lot of attention in recent years [4244]. …”
Section: Introductionmentioning
confidence: 99%